Attack On Pinjol: Who's Wrong Between Pinjol and Debtor - Andi Ahmad Faisal; Rizkyansyah Ramadhan; Muhammad Daniel Adhitama; Dang Anzala Ajra Akbar; Mardianto Albertus Simarmata; Aditya Wiradimadja (Cinematology: Journal Anthology of Film and Television Studies, 2022)
Human life and activities in this era of globalization are increasingly modern and bound by technology.  The fintech concept itself is an adjustment to advances in digital technology in the financial sector, especially in the banking world.  Financial technology is an innovation related to financial services and technology, in which there are new applications, processes, products or models that aim to facilitate the community.  One form of fintech is Peer to peer lending, which is an information technology-based money-borrowing service between the Recipient and the Lender, which is also known as an online loan or abbreviated as lender.  Peer to peer lending services can be accessed by the public through applications quickly, anytime and anywhere.  The convenience in online loans also poses a big risk, where there are many illegal online loan service providers with the characteristics of easy loan application requirements, aggressive marketing methods, applying short loan tenors, not having clear interest calculation rules and  usually charge higher interest rates above 0.8% per day, billing procedures using threats and violence that deviate from legal and humanitarian norms, as well as a code of ethics as conveyed by AFPI.  the loan application has a system structure, where every illegal loan application has a parent, namely a legal loan application.  One parent can have 20 to 40 child applications.  Online loan applications can also access user data and misuse it, where when a debtor borrows money in a parent application, there will be another disbursement of funds in another child application using the borrower's data without the borrower knowing.